Anti-Corruption Culture in Traditional Societies: A Case Study of Indigenous Wisdom and Governance - Ansori; Zohaib Hassan Sain (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
This research aims to explore the role of traditional cultural values ​​in building an anti-corruption culture, examine the relationship between anti-corruption culture in Indigenous communities and the concept of sustainable development, and understand the implementation of religious and cultural values ​​in fostering anti-corruption attitudes. Using the literature review system method, this research analyzes various literature related to anti-corruption cultural practices in indigenous communities in Indonesia. The research results show that traditional values ​​such as honesty, cooperation, and collective responsibility are a strong foundation for preventing corruption. In addition, the anti-corruption culture of Indigenous communities is closely relevant to sustainable development, covering economic, social, and cultural aspects. Implementing religious values ​​combined with traditional traditions creates an integrative system that effectively prevents corrupt behavior. This research provides implications for developing policies based on local culture to strengthen the integrity and sustainability of society.